Studies on the Australian stick insect genus Ctenomorpha Gray (Phasmida: Phasmatidae: Phasmatinae), with the description of a new large species - Hasenpusch, Jack; Brock, Paul D. (Zootaxa, 2006)
The little-known Australian genus Ctenomorpha Gray, 1833 is reviewed and an extraordinarily large species from north Queensland Ctenomorpha gargantua spec. nov. described. Variability of the type species, Phasma (Ctenomorpha) marginipennis Gray, 1833 is discussed and a lectotype designated. Lectotypes are also designated for Acrophylla aliena Redtenbacher, 1908, Acrophylla oxyacantha Redtenbacher, 1908 and Acrophylla phyllocerca Redtenbacher, 1908. Several insects previously listed as Ctenomorpha species are treated as follows: Ctenomorpha acheron Gray, 1834 is synonymised with Eurycnema goliath Gray, 1834, Ctenomorpha macleayi Gray, 1835 is synonymised with Ctenomorphodes briareus Gray, 1834, Acrophylla salmacis Westwood, 1859 is synonymised with Eurycnema osiris (Gray, 1834). Anchiale marmorata (Redtenbacher, 1908) comb. nov. is transferred from Ctenomorpha (originally described in Acrophylla Gray, 1835), Acrophylla aliena Redtenbacher, 1908 stat. rev. is returned to its original genus, from Ctenomorpha, whilst Phibalosoma caprella Westwood, 1859 is left as a doubtful Australian species, requiring transfer to another genus in due course. Keys to Ctenomorpha species are provided.